2021
DOI: 10.1186/s12864-021-07539-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome analysis of probiotic product isolates reveals the presence of genes related to antimicrobial resistance, virulence factors, and toxic metabolites, posing potential health risks

Abstract: Background Safety issues of probiotic products have been reported frequently in recent years. Ten bacterial strains isolated from seven commercial probiotic products on market were evaluated for their safety, by whole-genome analysis. Results We found that the bacterial species of three probiotic products were incorrectly labeled. Furthermore, six probiotic product isolates (PPS) contained genes for the production of toxic metabolites, while anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 57 publications
1
29
0
1
Order By: Relevance
“…The 4 strains contained genes related to bile stress like cbh (K01442) encoding for choloylglycine hydrolase. Additionally, it was previously reported that bsh genes were closely related to the formation of precipitate circles observed in the study for the BSH activity assay ( Wang G. et al, 2021 ). The 4 predicted bile salt hydrolase ( bsh ) genes have been identified in L. plantarum ST-III.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The 4 strains contained genes related to bile stress like cbh (K01442) encoding for choloylglycine hydrolase. Additionally, it was previously reported that bsh genes were closely related to the formation of precipitate circles observed in the study for the BSH activity assay ( Wang G. et al, 2021 ). The 4 predicted bile salt hydrolase ( bsh ) genes have been identified in L. plantarum ST-III.…”
Section: Resultsmentioning
confidence: 57%
“…The available functional evaluation methods mainly include in vitro tests, in vivo tests, and human clinical studies ( Koirala and Anal, 2021 ). As high-throughput sequencing technology is becoming more affordable, genomic analysis is an expected method for accurate strain identification and functional prediction for probiotics ( Wang Y. et al, 2021 ). The combination of characteristic experiments and genetic information of candidate strains has the potential to promote the evaluation system of probiotics ( Huang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of reports showing that the development of antibiotic resistance under conditions of selective pressure in commensals can be accompanied not only by point mutations of target proteins but also by large-scale genomic rearrangements associated with the resistome and mobilome as well as the evolution of virulence is growing ( 3 8 ). In this regard, the analysis of the genomes of probiotic bacteria with respect to the resistome, mobilome, and virulome is the focus of attention today ( 10 , 13 , 14 , 64 , 65 ), but systematic studies aimed at verifying the assumption regarding the evolution of virulence in these bacteria under conditions of selective antibiotic pressure are not yet available. We found that increased resistance to popular antimicrobial drugs in L. plantarum is accompanied by significant changes in the genomic profile and phenotypic sensitivity to a number of antimicrobial drugs as well as in the level of virulence of this bacterium against Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that in addition to studying the beneficial properties of lactic acid bacteria, considerable attention should be directed to assessing the virulence of microorganisms as well as investigating the possibility of its evolution under conditions of selective pressure of antimicrobials ( 12 ). To assess the virulence of probiotics, it is now recommended to analyze the genomes of bacteria in relation to the profiles of the virulome, resistome, and mobilome as well as the analysis of phenotypic resistance and virulence in vitro ( 3 , 13 , 14 ). However, the corresponding procedure has not yet been standardized, and the virulence analysis of strains in vivo using model organisms has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, phylogenomics paired with comparative genomics facilitate the taxonomic classification of isolates, pinpoint putative probiotic markers, and provide information about their fermentation profile and niche preference ( Pan et al, 2021 ; Surve et al, 2022 ). Furthermore, genome mining helps toward the identification of virulence phenotypes and resistance to common antibiotics, offering valuable insights into potential health hazards associated with their consumption ( Wang et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%